Induction of interleukin 21 receptor expression via enhanced intracellular metabolism in B cells and its relevance to the disease activity in systemic lupus erythematosus - Yoshiya Tanaka; Satoshi Kubo; Hiroko Miyata; Shingo Nakayamada; Kaoru Yamagata; Yusuke Miyazaki; Ippei Miyagawa; Shigeru Iwata; Ryuichiro Kanda; Koshiro Sonomoto; Yasuyuki Todoroki; Masanobu Ueno; et al. (RMD Open)
Objective To elucidate the association between the changes in intracellular metabolism in the early stage of B cell activation and systemic lupus erythematosus (SLE) pathogenesis.Methods CD19+ or CD19+CD27- (naïve) cells from the peripheral blood of healthy controls and lupus patients were cultured under different stimuli. The changes in intracellular metabolism and signalling pathways in these cells were evaluated.Results Stimulation with CpG (Toll-like receptor 9 (TLR9) ligand) in vitro induced enhanced interleukin 21 (IL-21) receptor expression in CD19+CD27- cells after 24 hours. The addition of IL-21 to the CpG stimulation enhanced the extracellular acidification rate, which indicates glycolysis, within 30 min. IL-21 receptor (IL-21R) expression induced by CpG stimulation was selectively inhibited by 2-deoxy-D-glucose (hexokinase 2 (HK2) inhibitor) and heptelidic acid (glyceraldehyde 3-phosphate dehydrogenase (GAPDH) inhibitor). RNA immunoprecipitation with anti-GAPDH antibody revealed that CpG stimulation dissociated the binding between IL-21R messenger RNA (mRNA) and GAPDH under no stimulation. HK2 and GAPDH expression were higher in CD19+CD27- cells of lupus patients than in those of healthy controls, and GAPDH expression was correlated with the plasmocyte count and disease activity score.Conclusion IL-21R mRNA-GAPDH binding dissociation associated with rapid glycolytic enhancement by the TLR9 ligand in B cells may induce plasmocyte differentiation through IL-21 signals and be involved in exacerbating SLE.